2000
DOI: 10.1046/j.1365-2745.2000.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Root hemiparasites and plant diversity in experimental grassland communities

Abstract: Summary1 We studied the relationship between the diversity of grassland communities and the eects of the generalist hemiparasitic plant Rhinanthus alectorolophus. We compared resistance against biomass loss as a consequence of infection, performance of the parasite and resistance of the parasitized communities to invasion by other plant species. Seeds of the parasite were sown into experimental plots containing 1, 2, 4, 8 or 32 plant species belonging to one or more of three functional groups (grasses, legumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
132
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 143 publications
(145 citation statements)
references
References 57 publications
(87 reference statements)
11
132
1
Order By: Relevance
“…Our experiment confirms previous findings, that experimental communities with higher numbers of resident species are more resistant to invasion from both internal and external invaders than species-poor communities (Tilman 1997, Knops et al 1999, Joshi et al 2000, Levine 2000, Naeem et al 2000, Hector et al 2001, Kennedy et al 2002, Fargione et al 2003, van Ruijven et al 2003, Pfisterer et al 2004, Maron and Marler 2008, Roscher et al 2009a). We also found that the invasion process was highly non-random on the functional group level.…”
Section: Invasibility and Invasivenesssupporting
confidence: 92%
“…Our experiment confirms previous findings, that experimental communities with higher numbers of resident species are more resistant to invasion from both internal and external invaders than species-poor communities (Tilman 1997, Knops et al 1999, Joshi et al 2000, Levine 2000, Naeem et al 2000, Hector et al 2001, Kennedy et al 2002, Fargione et al 2003, van Ruijven et al 2003, Pfisterer et al 2004, Maron and Marler 2008, Roscher et al 2009a). We also found that the invasion process was highly non-random on the functional group level.…”
Section: Invasibility and Invasivenesssupporting
confidence: 92%
“…The buffering of ID by functional diversity of hosts suggests that the deficits of inbred R. alectorolophus may be better compensated for if hosts from different functional groups are available. This supports the view that for hemiparasites such as R. alectorolophus the diversity of communities is of particular importance (Marvier and Smith, 1997;Joshi et al, 2000).…”
Section: Inbreeding Depression and Stress By Poor Host Qualitysupporting
confidence: 79%
“…Sites differed widely in climate, soil conditions, and other major environmental factors (Hector et al 1999, Joshi et al 2001. For more detailed information on single sites, for Switzerland see Diemer et al (1997), Joshi et al (2000), Koricheva et al (2000), Spehn et al (2000a, b), Stephan et al (2000), Diemer and Schmid (2001), Pfisterer et al (2004); for Sweden see Mulder et al (1999Mulder et al ( , 2002, Koricheva et al (2000), and Jumpponen et al (2002); for Germany see Gastine et al (2003) and Scherer-Lorenzen et al (2003); for Greece see Troumbis et al (2000Troumbis et al ( , 2002; for Portugal see Caldeira et al (2001); and for Silwood see Hector et al (2000aHector et al ( , 2001a.…”
Section: Study Sitesmentioning
confidence: 99%